A framework for interest-based community evolution and sharing of latent knowledge. (1st January 2012) - Pandey, Mayank; Pathak, Varun Kumar; Chaudhary, Banshi Dhar
The Government of India has taken initiative to establish a National Knowledge Network (NKN) to promote collaborative research and knowledge sharing. The knowledge to be shared is distributed on the nodes situated behind proxies/NATs of different institutions which are not visible to outside world. We term such knowledge as latent knowledge. In this paper we present the design and implementation of publish/subscribe system over hierarchical structured peer-to-peer (P2P) overlay for evolution and management of interest-based communities over NKN. Our hierarchical DHT has three tiers and it permits dynamic leaving and joining of peers and their migration between tiers. We have developed semantically enriched content-based publish/subscribe over our three-tier DHT using domain ontology for sharing latent knowledge. The simulation results establish the applicability of our approach. Further, we present the details of our prototype implementation which have been successfully tested and made operational in two geographically separated organisations connected by NKN.